TRAF3IP3 promotes glioma progression through the ERK signaling pathway - Lin, Qi; Chen, Zhen; Shen, Zhao-Li; Xue, Fei; Qin, Jia-Jun; Kang, Xi-Peng; Chen, Zhong-Rong; Xia, Zhong -Yuan; Gao, Liang; Chen, Xian-Zhen (Frontiers in Oncology, 2022)
Background. TRAF3IP3 was reported to associated with poor prognosis in melanoma, while its role in glioma is unknown. We aimed to demonstrate the relationship between TRAF3IP3 and glioma and investigate the potential role of TRAF3IP3 in glioma. Methods. Patients with glioma were collected from TCGA and GEO database. We compared the expression of TRAF3IP3 in glioma and normal tissues with wilcoxon rank sum test, and logistic regression was used to evaluate the relationship between TRAF3IP3 and clinicopathological characters. Moreover, Kaplan-Meier was performed to evaluate the correlation between TRAF3IP3 and survival rate. Gene set enrichment analysis (GSEA) was used to annotate biological function of TRAF3IP3 in glioma. We also examined the effect of TRAF3IP3 on the progression of glioma, including cell proliferation, migration, and invasion, and determined its underlying molecular mechanism using glioma cell lines and mouse xenograft models. Results. High TRAF3IP3 expression in glioma was associated with person neoplasm cancer statues, tissue source site. High TRAF3IP3 expression had a poorer overall survival (OS) (P=0.03), which were validated in the TCGA. TRAF3IP3 expression was correlated with OS. GSEA showed that the enrichment of Neuroactive ligand receptor interactions, proteasome pathway, and Calcium signaling pathway in the TRAF3IP3 high expression phenotype. We found the knockdown of TRAF3IP3 markedly suppressed the proliferation, migration, and invasion of U251 glioma cells, whereas the overexpression of TRAF3IP3 notably promoted tumor progression in U118 glioma cells. Mechanism research revealed that TRAF3IP3 upregulated p-ERK expression in glioma cells. Notably, ERK signaling pathway inhibitor U0126 dramatically attenuated the effects of TRAF3IP3 on p-ERK. Moreover, U0126 remarkably blocked the tumor-promoting activity of TRAF3IP3. The overexpression of TRAF3IP3 also promoted the proliferation in vivo tumor growth in a nude mouse xenograft model. Collectively, TRAF3IP3 promoted glioma cell proliferation, migration, and invasion, at least in part, by activating ERK signaling pathway. Conclusions. High TRAF3IP3 expression in glioma was correlation with poorer overall survival. Elevated TRAF3IP3 expression may be a potential biomarker for the prognosis of glioma. Moreover, TRAF3IP3 might participate in the development of glioma via ERK signaling pathway.